Naqshbandiyah And Spiritual Approaches In Determining The Beginning Of The Hijrah Month - Muhajir, Muhajir; Khusniyah, Anisaul; Nursoleh, Muhammad Afda Afif; Azizah, Zahra (CV. ULIL ALBAB CORP, 2025)
The determination of the beginning of the Hijri month is one of the essential aspects, in determining the implementation of worship that has a distinctive approach in determining the beginning of the Hijri month, is the Naqshbandiyah Tarekat Naqsyabandiyah. The Naqshbandiyah Order is known for its spiritual teachings, which in determining the beginning of the Hijri month must involve spiritual experience and a deep appreciation of religious teachings. This is what distinguishes it from the methods used by the government in general. This study aims to explore the methods used by the adherents of the Naqsyabandiyah Order in determining the beginning of the Hijri month, using the Literature research method. The Literature Research Method is carried out by digging up various literature related to the Naqsyabandiyah Tarekat and the determination of the beginning of the Hijri month. The interpretation of this study shows that the Naqsyabandiyah Tarekat uses a combination of methods in determining the beginning of the Hijri month, namely Hisab and Rukyat which are based on their spiral beliefs. However, there are drawbacks in using this method, such as reliance on estimates and lack of accurate use of tools, which can affect the accuracy of determining the beginning of the Hijri month. This study also identifies that the difference in methods used between the Naqsyabandiyah Tarekat and the Government often results in a difference in the time of the beginning of the month. This research is expected to contribute to understanding the dynamics of determining the beginning of the hijri month.